Pemanfaatan Biogas Skala Rumah Tangga Sebagai Sumber Energi Alternatif Berkelanjutan - Sawithri Raudhatunnisa; Lailal Gusri (JURNAL ILMIAH NUSANTARA, 2025)
Climate change, driven by increasing greenhouse gas emissions, demands the diversification of cleaner and more sustainable energy sources, including at the household level. Jambi City, which faces the challenges of fossil fuel dependence and high organic waste production, has great potential for the development of biogas as a renewable energy source. The study aimed to evaluate potential feedstocks, production capacity, digester efficiency, and the economic and environmental benefits of biogas use in households. The research method employed a mixed quantitative and qualitative approach, utilizing surveys, interviews, observations, and literature reviews. The study results indicate that domestic and commercial organic waste in Jambi City, with a volume of 333.6 tons per day, can be processed to obtain sufficient biogas to meet domestic cooking energy needs. A simple facility based on livestock manure or organic waste has proven to be technically and economically effective, with a positive benefit-cost ratio (B/C) and significant energy savings potential of 1.23, along with a payback period of 3.5 years. However, challenges such as high initial costs, lack of technical expertise, and fluctuations in raw materials remain significant obstacles. Replication strategies through community training, institutional support, and crowdfunding schemes are key to increasing the scalability and sustainability of biogas utilization in Jambi City.